Hemodynamic Features of Symptomatic Vertebrobasilar Disease. Issue 7 (July 2015) - Amin-Hanjani, Sepideh; Du, Xinjian; Rose-Finnell, Linda; Pandey, Dilip K.; Richardson, DeJuran; Thulborn, Keith R.; Elkind, Mitchell S.V.; Zipfel, Gregory J.; Liebeskind, David S.; Silver, Frank L.; Kasner, Scott E.; Aletich, Victor A.; et al.
Abstract : Background and Purpose—: Atherosclerotic vertebrobasilar disease is an important cause of posterior circulation stroke. To examine the role of hemodynamic compromise, a prospective multicenter study, Vertebrobasilar Flow Evaluation and Risk of Transient Ischemic Attack and Stroke (VERiTAS), was conducted. Here, we report clinical features and vessel flow measurements from the study cohort. Methods—: Patients with recent vertebrobasilar transient ischemic attack or stroke and ≥50% atherosclerotic stenosis or occlusion in vertebral or basilar arteries (BA) were enrolled. Large-vessel flow in the vertebrobasilar territory was assessed using quantitative MRA. Results—: The cohort (n=72; 44% women) had a mean age of 65.6 years; 72% presented with ischemic stroke. Hypertension (93%) and hyperlipidemia (81%) were the most prevalent vascular risk factors. BA flows correlated negatively with percentage stenosis in the affected vessel and positively to the minimal diameter at the stenosis site ( P <0.01). A relative threshold effect was evident, with flows dropping most significantly with ≥80% stenosis/occlusion ( P <0.05). Tandem disease involving the BA and either/both vertebral arteries had the greatest negative impact on immediate downstream flow in the BA (43 mL/min versus 71 mL/min; P =0.01). Distal flow status assessment, based on an algorithm incorporating collateral flow by examining distal vessels (BA and posterior cerebral arteries), correlated neither with multifocality of disease nor with severity of the maximal stenosis. Conclusions—: Flow in stenotic posterior circulation vessels correlates with residual diameter and drops significantly with tandem disease. However, distal flow status, incorporating collateral capacity, is not well predicted by the severity or location of the disease. Abstract : Supplemental Digital Content is available in the text.